Myth and Ideology in Quraysh’s Reaction to Umar bin Khattab's Conversion: A Semiotic Analysis of the Film “مسلسل عمر- الحلقة 8” - Rozana, Isyti Aisyan; Hakim, Arif Rahman (Makassar State University, 2025)
Abstract. This study aims to reveal the forms of ideological myths in a colossal religious film entitled “مسلسل عمر- الحلقة 8 ” produced by qatar in 2012 and uploaded to youtube account in 2020 where the focus of the research lies on the reaction of the quraisy mekah to Umar bin Khattab's entry into Islam based on Roland Barthes' semiotic perspective. This is motivated by the phenomenon of people just being movie lovers without paying attention and understanding more deeply the symbols or signs that may contain more complex meanings than just a show so that it can affect people's thinking paradigms. The type of this research is qualitative. The data used comes from a colossal religious film entitled “مسلسل عمر- الحلقة 8 ” on the qatar youtube account in 2020. The data were collected using the watch, listen, and record techniques, while the data analysis followed the Miles and Huberman model in the form of data reduction, data presentation in the form of narrative dialog, and conclusion drawing based on the research objectives. The findings of this study explain how individual spiritual events such as Umar bin Khattab's conversion to Islam are elevated to collective symbols, then mythologized by the old rulers (the Quraysh) to maintain their ideology and hegemony. The myth makes the event appear as a “betrayal of nature” but in fact it is just a cultural interpretation wrapped up as if it were natural. This shows that the myth built in the reaction of the quraisy of Mecca to Umar's Islam is not just emotional spontaneity, but part of a form of ideological naturalization in an effort to maintain hegemony, social order, and old belief doctrines. The forms of myths found in the film based on Roland Barthes' semiotics consist of six: the myth that conversion must be done secretly, change shows betrayal, the solidity of paganism is collapsing, Islam adherents only come from the weak and lower castes, transformation occurs instantly, and prophetic claims must have worldly privileges and meet the standards of human expectations. This reveals a new perspective that prophetic legitimacy is mythologized through worldly expectations, that religious authority in classical Islamic narratives can be shaped by social and cultural constructs rather than solely by divine criteria through Barthes' mythical semiotics—a perspective that is rarely explored in the study of religious media semiotics.Keywords: : Myth, Ideology, Quraysh Reaction, مسلسل عمر- الحلقة 8, Roland Barthes